Pengaruh Kompetensi Kepribadian Guru Terhadap Motivasi Belajar Peserta Didik di Sekolah Dasar - Linda, Linda Agustina; Alif Luthvi Azizah; Fitriadi; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the low learning motivation of elementary school students, which is reflected in students lack of interest in learning activities, low active participation during lessons, and insufficient internal drive to achieve optimal learning outcomes. This condition is presumed to be closely related to teachers personality competence, considering that teachers play a strategic role as educators, mentors, and role models in the learning process. Teachers with strong personality competence are expected to create a conducive, engaging, and motivating learning environment that encourages students to learn more effectively.This study aims to determine the effect of teachers personality competence on students learning motivation in elementary schools. The research employed a quantitative approach using an ex-post facto research design, which seeks to identify causal relationships based on existing conditions without providing specific treatments to the research subjects. The population of this study consisted of all fifth-grade students in the elementary school, totaling 44 students. A saturated sampling technique was applied, meaning that the entire population was used as the research sample. Data were collected using a non-test technique in the form of questionnaires designed to measure teachers personality competence and students learning motivation. The collected data were then analyzed using simple linear regression analysis to test the research hypothesis. The results of the hypothesis testing showed that H₁ was accepted and H₀ was rejected. Therefore, it can be concluded that teachers personality competence has a significant effect on students learning motivation in elementary schools. Based on the findings of this study, it is evident that teachers personality competence has a positive influence on students’ learning motivation, indicating that the better the teachers’ personality competence, the higher the students’ learning motivation